2011
DOI: 10.13073/0015-7473-61.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Purchase Decision: Sustainability of Mountain Pine Beetle Wood Concrete Products

Abstract: In British Columbia, many communities are dependent on the forest industry and are consequently concerned about uses for the millions of hectares of pine forests killed by the mountain pine beetle. The wood fiber from those dead trees is normally useless for traditional manufacturing of dimensional lumber due to its fragility and poor quality, but wood concrete provides an alternative use. This was a market research study on mountain pine beetle wood concrete product (MPBWCP), an innovative wood product that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This may be attributed to the increasingly complex decisions consumers face in order to engage in sustainable lifestyle choices [2]. Consumption behaviors related to more specific products have found that socio-demographics do play a role when characterizing consumer segments for therapeutic foods [35], sustainable apparel [36,37], sustainable wood products [38], sustainable convenience foods [39], food supplements [40], and alternative medicine [41]. Hemp has emerged as an ingredient in all of these products.…”
Section: Literature Review: Sustainable Consumptionmentioning
confidence: 99%
“…This may be attributed to the increasingly complex decisions consumers face in order to engage in sustainable lifestyle choices [2]. Consumption behaviors related to more specific products have found that socio-demographics do play a role when characterizing consumer segments for therapeutic foods [35], sustainable apparel [36,37], sustainable wood products [38], sustainable convenience foods [39], food supplements [40], and alternative medicine [41]. Hemp has emerged as an ingredient in all of these products.…”
Section: Literature Review: Sustainable Consumptionmentioning
confidence: 99%
“…The conjoint analysis method has also been applied in forest certification consumer market research (e.g. Bigsby and Ozanne 2002;Anderson and Hansen 2004a, Anderson and Hansen 2004b, Anderson et al 2005, Roos and Hugosson 2008Thompson et al 2010;Choi et al 2011). For example, Anderson and Hansen (2004a) detected a more than 30% drop in market share when a certified product was offered at a 2% premium over a non-certified option.…”
Section: State Of Art In the Literature Of Consumer Values And Trendsmentioning
confidence: 99%
“…Importing forest products into Central America may be necessary to meet the growing demand for building materials because of an increase in population, tourism, and deforestation (Fallas 2008; Rogers 2009; World Bank 2010; Montagnini et al 2003). Turner et al (2005) suggested that trade free agreements with Latin American countries might open the opportunity for forest products exporting countries to gain market share in the region. Current trade figures for Central American countries indicate an increased trend in the import of wood products.…”
Section: Introductionmentioning
confidence: 99%